Weak Solutions of Second Order Parabolic Equations in Noncylindrical Domains (Journal of Partial Differential Equations, 1989)
Penalization method is used to get the existence of the weak solutions or parabolic equations in noncylindrical domains. The asympcotic decay and the existence and uniqueness of the periodic solutions are obtained as well.